2020
DOI: 10.1111/1759-7714.13707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and survival following placement of self‐expandable metallic stents for central airway stenosis and fistula

Abstract: Significant findings of the study: mMRC grade, PS and symptoms improved after SEMS placement in 87.5% of patients with malignant CAS or CAF. Some patients were able to live longer because of effective therapies after SEMS placement. What this study adds: Patients with malignant central airway stenosis are usually terminal. Their lifespan can be lengthened by inserting SEMSs combined with new efficient therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The treatment and management of MCAS were very difficult until the time in which specific airway interventions were available, such as electrocautery, cold ablation, mechanical resection, laser, and airway dilatation [ 1 5 ]. MCAS can be rapidly resolved in most patients using therapeutic bronchoscopy [ 2 , 6 ]. However, airway restenosis commonly occurs after therapeutic bronchoscopy with the progress of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment and management of MCAS were very difficult until the time in which specific airway interventions were available, such as electrocautery, cold ablation, mechanical resection, laser, and airway dilatation [ 1 5 ]. MCAS can be rapidly resolved in most patients using therapeutic bronchoscopy [ 2 , 6 ]. However, airway restenosis commonly occurs after therapeutic bronchoscopy with the progress of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies have reported that patients with a poor ECOG PS have a short survival time after airway stenting (8,9). In contrast, SEMS placement in patients with a poor ECOG PS has been shown to be effective against malignant airway disorders (10). Another study reported improvements in airway intervention results, especially in patients with an ECOG PS 3-4, but did not include the AERO stent.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple approaches to improve airway stenosis in malignant CAO patients, including mechanical debulking, cryotherapy, thermal therapy, and airway stent implantation (14)(15)(16). The metallic airway stent is a crucial treatment method for malignant airway stenosis, which is part of multimodal approach in malignant CAO patients (17)(18)(19). However, there are some limitations in the implantation procedures of previous stents, which should be implanted under X-ray or rigid/flexible bronchoscope visualization.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some limitations in the implantation procedures of previous stents, which should be implanted under X-ray or rigid/flexible bronchoscope visualization. This is time-consuming and requires unnecessary radiation exposure and higher technical conditions (16)(17)(18)(19). Our previous pilot study demonstrated the preliminary application of a novel metallic airway stent in CAO patients (13), which could be inserted into the scope of a flexible bronchoscope and be implanted under direct visualization.…”
Section: Discussionmentioning
confidence: 99%